The Impact of Theory X and Theory Y on Organization Performance in the Private Banking Sector of Sindh, Pakistan - Nazia Dharejo; Noor un Nisa Shahani; Aqsa Dharejo (International Journal of Business and Economic Affairs, 2022)
This study investigated the Impact of Theory X and Theory Y on the organizational performance of the private banking sector in Sindh, Pakistan. This research is based on the quantitative research methodology, for which a convenient sampling type of non-probability technique was used, and the particular staff was targeted for data collection. Staff members were categorized into three levels with the help of quota sampling. Data was collected through close-ended questionnaires with the use of the 7-points Likert Scales. A total of 150 questionnaires were distributed, out of which 130 questionnaires were returned 110 questionnaires were considered for analysis finally. For data analysis, SPSS version 22.0 software was used to test the relationship among variables (Organization Performance, Theory X, and Theory Y). The employees must be very knowledgeable about the various issues of the organization, as well as he or they must possess the competence to make decisions that benefit the organization. Different types of employees and their personalities have a significant impact on organizational performance; therefore, identifying them is crucial for management. This research will be helpful for practitioners to identify and assess their overall impact on the organization’s performance. The result showed that all items were effectively accepted in the measurement of three factors for the hypotheses created, including Theory X, Theory Y, and Organization Performance.